Meet me at the lake - Fortune, Carley (Berkley Romance, 2023)
"Fern Brookbanks has wasted far too much of her adult life thinking about Will Baxter. She spent just twenty-four hours in her early twenties with the aggravatingly attractive, idealistic artist, a chance encounter that spiraled into a daylong adventure in Toronto. The timing was wrong, but their connection was undeniable: they shared every secret, every dream, and made a pact to meet one year later. Fern showed up. Will didn't. At thirty-two, Fern's life doesn't look at all how she once imagined it would. Instead of living in the city, Fern's back home, running her mother's Muskoka lakeside resort-something she vowed never to do. The place is in disarray, her ex-boyfriend's the manager, and Fern doesn't know where to begin. She needs a plan-a lifeline. To her surprise, it comes in the form of Will, who arrives nine years too late, with a suitcase in tow and an offer to help on his lips. Will may be the only person who understands what Fern's going through. But how could she possibly trust this expensive-suit wearing mirage who seems nothing like the young man she met all those years ago. Will is hiding something, and Fern's not sure she wants to know what it is. But ten years ago, Will Baxter rescued Fern. Can she do the same for him?"--